Human TLR8 senses UR/URR motifs in bacterial and mitochondrial RNA. (6th November 2015) - Krüger, Anne; Oldenburg, Marina; Chebrolu, Chiranjeevi; Beisser, Daniela; Kolter, Julia; Sigmund, Anna M; Steinmann, Jörg; Schäfer, Simon; Hochrein, Hubertus; Rahmann, Sven; Wagner, Hermann; Henneke, Philipp; et al.
Abstract: Toll‐like receptor (TLR) 13 and TLR2 are the major sensors of Gram‐positive bacteria in mice. TLR13 recognizes Sa19, a specific 23S ribosomal (r) RNA‐derived fragment and bacterial modification of Sa19 ablates binding to TLR13, and to antibiotics such as erythromycin. Similarly, RNase A‐treated Staphylococcus aureus activate human peripheral blood mononuclear cells (PBMCs) only via TLR2, implying single‐stranded (ss) RNA as major stimulant. Here, we identify human TLR8 as functional TLR13 equivalent that promiscuously senses ssRNA. Accordingly, Sa19 and mitochondrial (mt) 16S rRNA sequence‐derived oligoribonucleotides (ORNs) stimulate PBMCs in a MyD88‐dependent manner. These ORNs, as well as S . aureus‐, Escherichia coli‐, and mt‐RNA, also activate differentiated human monocytoid THP‐1 cells, provided they express TLR8. Moreover, Unc93b1 −/− ‐ and Tlr8 −/− ‐THP‐1 cells are refractory, while endogenous and ectopically expressed TLR8 confers responsiveness in a UR/URR RNA ligand consensus motif‐dependent manner. If TLR8 function is inhibited by suppression of lysosomal function, antibiotic treatment efficiently blocks bacteria‐driven inflammatory responses in infected human whole blood cultures. Sepsis therapy might thus benefit from interfering with TLR8 function. Synopsis: This study shows that human monocyte TLR8 senses bacterial ribosomal and transfer RNA, as well as mitochondrial RNA. TLR8 recognizes a UR/URR RNA‐ligand consensus motif in contrast to the bacteria‐borne 10‐mer motif detected by its murine TLR13 counterpart. Various molecular subpopulations of both Gram‐positive and Gram‐negative bacterial RNAs activate endosomal human TLR8. Large (16S) ribosomal mitochondrial RNA sequence‐derived oligoribonucleotides and total mitochondrial RNA activate human TLR8. TLR8 mediates human monocyte activation upon S . aureus and E . coli infection besides TLR2. Lysosomal inhibition by chloroquine largely impairs bacterial infection‐driven immune activation ex vivo . Abstract : This study shows that human monocyte TLR8 senses bacterial ribosomal and transfer RNA, as well as mitochondrial RNA. TLR8 recognizes a UR/URR RNA‐ligand consensus motif in contrast to the bacteria‐borne 10‐mer motif detected by its murine TLR13 counterpart.